Efficacy of salinomycin, monensin and lasalocid against spontaneous eimeria infection in rabbits - Pakandl, M (Folia parasitologica, 1986)
Rabbits spontaneously infected with coccidia of the genus Eimeria were treated with salinomycin, lasalocid and monensin. The drugs were applied in pellets in the doses of 50 ppm. The weight gain in rabbits treated with salinomycin and monensin was higher than in those treated with lasalocid and by 22.6% higher than in control animals. The weight gain in animals treated with lasalocid was almost the same as in the control group. The oocyst production was suppressed most significantly by salinomycin.
Keywords: Monensin; Coccidiostats; lasalocid; Pyrans; kokcidiostatika; zvířata; pyrany; králíci; monensin; kokcidióza; Rabbits; Coccidiosis; Lasalocid; Animals